Learning Model Based on Information Technology in an Accounting Education Courses Based on Technology at Faculty of Economics in Universitas Negeri Semarang - Yoga Baswara, Satsya; Widhiastuti, Ratieh; Citra Dewi, Lita (KnE Social Sciences, 2020)
It cannot be denied, nowadays technology is an inseparable part of learning in the classroom and also in the business world. Because of this there are many employers hoping that accounting and accounting education students get teaching about information technology in the field of accounting when they go to college. To fulfill this, in the College in the major of Accounting and Accounting Education curriculum, there are courses called accounting information systems (AIS), Computer Accounting and Introduction to Computer Accounting. This course, if traced back to its origin as mentioned above, is actually one of the very strategic courses. Why is it called very strategic value, because it is closely related to the development of information technology and the demands of the work world that are increasingly here becoming borderless? The teaching curriculum can be very different between each university depending on who and how the subject is coordinated. So that by using information technology learning instruments in the field of accounting developed by Wilis (2016), this study aims to examine a model of how to teach these courses in accounting education by incorporating the practice of using MS Excel in lecture meetings besides emphasizing the use of MS Visio. Keywords: information technology, computer-based learning, accounting education based on the information technology